An isotopic assessment of the water sourced by Ischyrolepis Sieberi (Restionaceae) growing at high altitudes in the Cedarberg : does fog play an important role? - Wigley, Benjamin (Department of Biological Sciences, 2017)
The main aim of this study was to determine if Ischyrolepis sieberi, a common restiod species found at high altitudes in the Cederberg captures fog to supplement its water needs. This was done by comparing the isotopic ratios of δD and δ¹⁸O in captured fog, rainwater, and stream water and comparing these to the δD and δ¹⁸O values found in the xylem water of Ischyrolepis sieberi plants growing at the study site. The δD values of the collected fog samples were enriched relative to rainwater, stream water, and xylem water from I. sieberi, however these differences were not significant. The δ¹⁸O values of the I. sieberi xylem water were significantly (p < 0.01) more enriched than rain, stream, and fog water. The xylem water of I. sieberi was depleted in δD and enriched in δ¹⁸O relative to all other water sources. The plants therefore did not appear to be utilizing fog during the three months of this study. The δ¹⁸O values of I. sieberi were consistently 4-6‰ enriched compared to rainwater, suggesting that they are utilizing rainwater, which has undergone fractionation due to evaporation in the soil before being taken up by the plants. This study was run during the wet winter months. The δD and δ¹⁸O values from previous data suggest that the I. sieberi plants do utilize fog during the dry summer months.